PENGARUH REVIEW BEAUTY INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN DI ERA PANDEMI COVID - 19 (Survei Pada Followers Instagram @hanummegaa) - Vina Ananda Nurlutfi, (2021)
The presence of instagram social media today encourages and creates the emergence of influencers. Influencer is a term for someone who has influence in shaping a person's opinions and attitudes. One of the influencer categories is beauty influencers, in which beauty influencers focus on creating product review content related to the world of beauty. Beauty product reviews give encouragement to women to decide to buy a beauty product, which is 64.7%. This study aims to see how much influence beauty influencer reviews have on purchasing decisions in the era of the Covid-19 pandemic. The theory used is cognitive response theory. This research uses quantitative research methods. This research was conducted for 10 months from October to July. The sample of this research is the followers of instagram @hanummegaa, amounting to 100 respondents. This study uses a questionnaire for data collection. The results showed that the influence of beauty influencer reviews on purchases in the Covid-19 pandemic era was based on hypothesis test with the results of t calculate 9.314 > 1.661 t table. The coefficient of determination shows the magnitude of the influence, namely 46.9% of the purchase decision is influenced by the beauty influencer review. The regression test results show the consistent value of variable Y is 1.919 while the regression coefficient X is 0.488. Based on these results, it can be said that the direction of the influence of the beauty influencer review (variable X) on purchasing decisions (variable Y) is said to be positive.